Gains and pitfalls of coalitions: Societal resources as sources of trade union power in Croatia and Poland - Butković, Hrvoje; Czarzasty, Jan; Mrozowicki, Adam (SAGE Publications)
This article explores the experiences of trade unions in Croatia and Poland with societal power resources as a source of trade union revitalisation in the post-2008 crisis period. In the context of limited structural, organisational and institutional power resources, Croatian and Polish trade unions attempted to build their societal power through the revitalisation strategies of coalition building and political action. The paper compares three similar, partially successful campaigns run in both countries, on pensions, Sunday trading and precarious work. Our findings show that gains in societal power alone cannot fully compensate for the erosion of conventional sources of trade union power. Such a configuration of power resources runs the danger of trade union demands being taken up by populist forces wanting to increase their own legitimacy, rather than furthering workers’ interests. Therefore, what starts as an attempt at union revitalisation based on the novel use of societal resources could easily end up as ‘captured innovation’ by populist forces.
Keywords: trade unions; power resoerces; societal power resorces; trade union revitalization; Croatia; Poland